Ground Fault Protection Using Open Break Delta Grounding Transformer in Ungrounded System - Supriyanto Suhono; Hari Purnama; Heri Budi Utomo (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2019)
One of the most common and difficult problems to solve in distribution power systems is the location and elimination of the ground fault. For the study of an electrical distribution network in ungrounded system operating at 20 kV on the primary and 380 V on the secondary. The model uses smaller nominal voltages consisting of 380 V on the primary and the secondary. The Ground fault protection system scheme uses over voltage relays and open break delta transformers, whereas for fault location detection using voltage transformers in star star connections.The highest single line to ground fault value is used for consideration of ballast rating selection. The single line to lowest ground fault value is used for setting the threshold on the voltage relay (59N). Referring to the result of the calculation of the highest single phase to ground voltage at point 1 is 144∠1800 volts, and the lowest point at 4 is 132∠1800 volts. A 200 ohm ballast impedance with 150 watts of power capacity, and an overvoltage threshold setting of 120 volts with TDS of 40. One phase fault protection mechanism works well at each point of interference, and voltage transformers are protected from overheating and damage.